1997
DOI: 10.1029/97rs00089
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Doppler interferometry and the measurement of atmospheric turbulence

Abstract: Abstract. Data taken by an imaging Doppler interferometer (IDI) 3.175-MHz radar during the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 27 publications
0
27
0
Order By: Relevance
“…The wind velocity variance relates to the TKE, provided that the non-turbulent contributions to that variance can be removed. A variety of radar techniques exist for estimating the wind velocity: from the line-of-sight velocity differences from meteors (Roper, 1966); from the imaging Doppler interferometry scattering positions (Roper and Brosnahan, 1997), from spaced antenna full correlation analysis (Briggs, 1980;Manson et al, 1981), and from the spectral broadening observed by MST Doppler radars. (Hocking, 1983).…”
Section: Radar Measurements Of the Turbulence Energeticsmentioning
confidence: 99%
“…The wind velocity variance relates to the TKE, provided that the non-turbulent contributions to that variance can be removed. A variety of radar techniques exist for estimating the wind velocity: from the line-of-sight velocity differences from meteors (Roper, 1966); from the imaging Doppler interferometry scattering positions (Roper and Brosnahan, 1997), from spaced antenna full correlation analysis (Briggs, 1980;Manson et al, 1981), and from the spectral broadening observed by MST Doppler radars. (Hocking, 1983).…”
Section: Radar Measurements Of the Turbulence Energeticsmentioning
confidence: 99%
“…Despite this agreement Holdsworth and Reid (1995b) were careful not to suggest that the volume scatter was applicable experimentally, or that the interferometric techniques would fail experimentally. However, Roper and Brosnahan (1997) and Turek et al (1998) appear to have interpreted the results as implying otherwise. Quoting verbatim from both: " Holdsworth and Reid (1995b) were unable to recover the actual scatterer positions and concluded that the scatterers identified by the IDI technique were fictitious."…”
Section: Imaging Doppler Interferometry and The Volume Scatter Situationmentioning
confidence: 94%
“…We therefore attribute the larger hourly estimated turbulent velocities to the effects of gravity waves, and suggest hourly (or larger) turbulent velocity estimates (e.g. Roper and Brosnahan, 1997) will be significantly overestimated.…”
Section: Long-term Velocity Comparisonsmentioning
confidence: 99%
See 1 more Smart Citation
“…Roper and Brosnahan [1997] (hereafter referred to as RB), in a development of the concept of the structure function representation of turbulence, with emphasis on e, the rate of dissipation of turbulent energy, assumed that the characteristic length Lo of the energy-bearing eddies was defined by the correlation coefficient of the characteristic velocity Uo falling to l/e, and arrived at the formula (their equation (2) The fact that the shears are larger at the smaller scales results in the disappearance of the smaller scales first, if the turbulence spectrum is decaying [Frisch, 1995]. This is pertinent to our later discussion of the intermittent, decaying turbulence responsible for the scatter which produces identifiable imaging Doppler interferometry (IDI) echoes.…”
Section: Turbulencementioning
confidence: 99%